EMPOWERMENT OF THE IMPORTANCE OF DIGITALIZATION ADAPTATION OF UMKM 'MANISAN MANGGO' IN CEMPAKA VILLAGE, TALUN DISTRICT, CIREBON REGENCY, WEST JAVA, INDONESIA - Ade Johar Maturidi; Lilis Suharti; Mohamat Setiawan; Syauqiyyah Salsabilauthor (Ann Publisher, 2024)
Cempaka Village is one of the villages located in Talun District, Cirebon Regency. The livelihood of the people of Cempaka Village is mostly to become laborers and farmers. However, there are also businesses such as grocery stores, street vendors, and home-based businesses. UMKM in Cempaka Village, Talun Regency itself show significant potential for the local economy. Candied mango is one of the products made by the people of Cempaka Village which is fairly capable of producing in large quantities and already has a fairly wide market share. However, in this case, mango candied UMKM still use conventional marketing which makes less widespread information and has not maximized the development of the digital era. One of the efforts made is to empower the importance of digitalization in mango candied UMKM in Cempaka village, namely by expanding access to information and marketing through making points on Google Maps and E-Commerce with the aim of increasing the marketing competitiveness of mango candied products.